Service and Reputation: An Examination of the Growth in Graduate Education at Public Master’s Universities - Kinne-Clawson, Alicia Marie (My University, 2017)
Public Master’s granting universities have long been viewed as a sector “caught in the middle” between their much more prestigious research university counterparts and the more numerous community colleges. The little research that exists on this sector of institutions has suggested that the Master’s university classification merely represents a way station to becoming a research university. Attainment of research university status is appealing because with it come significant resources, access to high quality faculty and a research enterprise, and legitimacy through increased political clout and, for many institutions, national rankings. Over the last several decades, public Master’s universities have evolved rapidly from their heritage as largely state teacher training academies. Just as their undergraduate enrollments have grown, so too, have their graduate enrollments. Alongside booming enrollments has been a slow increase in undergraduate selectivity, steady growth in state and federal grants and contracts for research, and the addition of new Master’s programs—and occasionally doctoral programs–at public Master’s universities. While many of these trends seem to indicate that institutions in this sector have been evolving towards the research university model, the volatile resource environment that these universities now operate in raises questions about the extent to which this is a viable strategy in the long-run. Using graduate enrollments as one indicator of pursuit of the research university model, this dissertation applies a mixed methods approach to create an enhanced understanding of the role and motivations behind the growth in recent decades of graduate enrollments at public Master’s universities. Drawing from institutional theory, resource dependency, and competitive strategy literature, and taking account of recent shifts in sources of financial support, this dissertation explores the extent to which graduate enrollment patterns at public Master’s universities serve as an indicator of their pursuit of the research university model or some other strategy. Below are the research questions guiding this mixed method study: 1. Pursuit of prestige: Are public master’s institutions making a strategic decision to grow graduate programs in order to raise their prestige and social legitimacy relative to other universities? Or, are there other important motivations behind this trend? 2. Resource dependency: Given the high costs associated with supporting graduate programs, are universities choosing to grow these enrollments in order to replace lost state support? Does revenue from graduate enrollment growth represent a sustainable business strategy? 3. Labor market: Is the growth in graduate enrollments the outcome of these traditionally regionally focused universities simply filling an unmet labor market need that is seen as consistent with their basic mission of teaching and local service? 4. Competitive strategy: To what extent are these universities growing graduate enrollments to compete more successfully with neighboring institutions? Or, to carve out a unique niche in the region that is currently underserved? 5. State/System governance: To what extent does an institution’s autonomy as measured through the policies of the state or system’s coordinating or governing board enable or impede the addition of new graduate programs at public Master’s universities? I find from this research that the factors enabling, and the motivations behind, the growth in graduate enrollments are a complex mix of the institutions’ resource environment, state policies and governing structures impacting institutional autonomy, and the condition of the state and local economy. The statistical analyses demonstrate evidence that public Master’s universities continue to rely on traditional sources of revenue (state funding and undergraduate tuition) in order to grow graduate enrollments. Likewise, the case studies highlighted the necessary conditions to grow graduate enrollments such as the importance of non-traditional revenue streams, for example self-sustaining program tuition revenue, as well as the significant challenges associated with growth. Taken together, this research emphasizes the difficulty of achieving pursuit of the research university model in the context of the current financial environment and establishes it as an exceptionally difficult and risky strategy to follow that is only likely to work in very particular circumstances.
Thesis (Ph.D.)--University of Washington, 2017-03
Keywords: Higher education; Higher education administration; Gender studies; To Be Assigned